PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMACHIEVEMENT DIVISION (STAD) DAN TIPE THINK PAIR SHARE (TPS) PADA MATERI POKOK SISTEM KOORDINASI MANUSIA KELAS XI SMA NEGERI 15 MEDAN - Alemi Charina Tarigan; Hasruddin Hasruddin (Jurnal Pelita Pendidikan, 2016)
This study aimed to compare the learning outcomes of students who were taught using STAD model ofTPS with the subject matter Coordination System In Humans in Class XI IPA at SMAN 15 Medan. This studycomprise the experimental study where the population is all students of Class XI IPA at SMAN 15 Medan, whichconsists of six classes with the number of 240 people. Random sampling (random sampling) and obtained twoclasses as a sample of Class XI IPA-5 and Class XI-6 totaling 79 people. Class XI IPA-5 are taught with the modeland grade XI TPS-6 is taught with STAD model. The instrument used in this study in the form of multiple choicequestions which amount to 25 pieces are used as a matter of pretest and posttest. The average resultsobtained for classroom learning TPS amounted to 80.51 higher than the class of STAD which amounted to 76.5so that there is a difference in value by 4.01%. Tests were performed by t test produces t_hitung = 2.409 and T_(table) = 1,665 with df = 77 and a significance level of 0.05. Based on the criteria H_o acceptable if - t_1 -½ α <t<t_1 - ½ α, then this study reject and accept. It can be concluded that there are differences in learningoutcomes of students who are taught by TPS cooperative model with STAD on the subject matter CoordinationSystem In Humans in Class XI IPA at SMAN 15 Medan and TPS are better than STAD on subject matterCoordination System In Human.Key Word : conventional method, computer-based media, learning outcome.